Taxonomic review of the genus Epilepia Janse, 1931 from China, with descriptions of two new species (Lepidoptera: Pyralidae, Epipaschiinae) - H. Rong; H. H. Li (SHILAP, 2017)
Three species of the genus Epilepia Janse, 1931 from China are reviewed. Epilepia denticulata Rong & Li, sp. n. and E. longaduncata Rong & Li, sp. n. are described as new. Photographs of adults and genitalia are provided.